Accelerated Hypofractionated Radiotherapy Versus Stereotactic Body Radiotherapy for the Treatment of Stage I Nonsmall Cell Lung Cancer—A Single Institution Experience With Long-Term Follow-Up. (12th October 2018) - Karasawa, Katsuyuki; Hayakawa, Sara; Machitori, Yumiko; Shibata, Yukiko; Ogawa, Hiroaki; Ito, Kei; Shimizuguchi, Takuya; Kawamoto, Terufumi; Nihei, Keiji
Purpose: Although stereotactic body radiation therapy is one of the standard treatments for stage I nonsmall cell lung cancer, in the case of central tumors it carries the risk of severe adverse events for serial organs. Accelerated hypofractionated radiotherapy is considered a reasonable alternative to treat central tumors. We have been treating central tumors with accelerated hypofractionated radiotherapy using a 75 Gy/25 fr/5 weeks regimen, and we compared the results with those of stereotactic body radiation therapy using 48 Gy/4 fr/1 week. Methods: Patients with central tumors and/or unfit for 1-hour fixation were candidates for accelerated hypofractionated radiotherapy. Based on the proximity to the biologically effective dose at 10 Gy, above accelerated hypofractionated radiotherapy regimen was adopted. Results: From October 2003 to December 2010, 159 patients, who received either accelerated hypofractionated radiotherapy (103 cases) or stereotactic body radiation therapy (56 cases), were included in the analysis. In the accelerated hypofractionated radiotherapy group, 40 (39%) cases were central tumors, whereas all cases were peripheral tumors in the stereotactic body radiation therapy group. Overall 5-year local control and survival rates were 81.9% (95% confidence interval 73.6%-90.1%) and 46.5% (95% confidence interval 36.7%-56.2%), respectively for the accelerated hypofractionated radiotherapy group, and 75.4% (95% confidence interval 63.0%-87.8%) and 44.6% (95% confidence interval 31.6%-57.7%), respectively for the stereotactic body radiation therapy group (n.s.). Among central tumors, ultracentral tumors (21 cases) and the remaining central tumors (19 cases) were similar in both local control and survival. On multivariate analysis, hazard ratios for accelerated hypofractionated radiotherapy versus stereotactic body radiation therapy were <1 for both local control and survival. Pulmonary toxicity was similar in both groups. No serial organ toxicity was observed for central tumors. Conclusions: Accelerated hypofractionated radiotherapy with a 75 Gy/25 fr/5 weeks regimen is promising in that it can obtain similar local control and survival results to stereotactic body radiation therapy, and it can control both central and peripheral tumors without any serial organ toxicities. Based on these results, prospective multicenter trials are worth conducting, especially for ultracentral tumors.